Loss of pyrethroid resistance in newly established laboratory colonies of Aedes aegypti. - Farah Z Vera-Maloof; Karla Saavedra-Rodriguez; Rosa P Penilla-Navarro; Americo D Rodriguez-Ramirez; Felipe Dzul; Pablo Manrique-Saide; William C Black (Public Library of Science (PLoS), 2020)
BACKGROUND:Resistance to pyrethroid insecticides in Aedes aegypti has become widespread after almost two decades of the frequent use of these pesticides to reduce arbovirus transmission. Despite this resistance, pyrethroids continue to be used because they are relatively inexpensive and have low human toxicity. Resistance management has been proposed as a way to retain the use of pyrethroids in natural populations. A key component of resistance management is the assumption that negative fitness is associated with resistance alleles such that resistance alleles will decline in frequency when the insecticides are removed. At least three studies in Ae. aegypti have demonstrated a decrease in pyrethroid resistance once the insecticide has been removed. METHODS/PRINCIPAL FINDINGS:The present study aims to evaluate variation in the loss of pyrethroid resistance among newly established laboratory populations of Ae. aegypti from Mexico. Eight field collections were maintained for up to eight generations, and we recorded changes in the frequencies of the mutations at the V1,016I locus and at the F1,534C locus in the voltage-gated sodium channel gene (VGSC). I1,016 and C1,534 confer resistance. We also examined resistance ratios (RR) with type 1 and 2 pyrethroids. CONCLUSIONS/SIGNIFICANCE:We demonstrate that, in general, the frequency of the Ae. aegypti pyrethroid-resistance alleles I1,016 and C1,534 decline when they are freed from pyrethroid pressure in the laboratory. However, the pattern of decline is strain dependent. In agreement with earlier studies, the RR was positively correlated with the frequencies of the resistance allele I1,016 and showed significant protection against permethrin, and deltamethrin, whereas F1,534C showed protection against permethrin but not against deltamethrin.